THE INFLUENCE OF STORY MAPPING STRATEGY AND READING HABIT TOWARDS READING COMPREHENSION ACHIEVEMENT OF THE EIGHTH GRADE STUDENTS OF SMP N 35 PALEMBANG - Rizka Amalia (ELTE Journal (English Languange Teaching and Education), 2019)
Abstract This study was to investigatethe influence of story mapping strategy and reading habit towards reading comprehension achievement of the eighth grade students of SMP N 35 Palembang. The population of this study was all theeighth grade students of SMP N 35 Palembang. The sample was 60 students (experimental class is consisted of 15 students’ high reading habit and 15 students’ low reading habit and control class is consisted of 15 students’ high reading habit and 15 students’ low reading habit) were taken by using two-stage random sampling. In carrying out the research, the writer used an experimental method; factorial design.The writer distributed test and reading habit questionnaire (high and low reading habit) in collecting the data. Then, in analyzing the data, the writer usedt-test and two-way ANOVA. The result of this study that; first, there was significant difference in reading comprehension achievement between the eighth grade students who had high reading habit and those who had low reading habit taught by using story mapping strategy. Second, there was significant difference in reading comprehension achievement between the eighth grade students who had high reading habit and those who had low reading habit taught byusing traditional teaching method. Third, there was significant difference in reading comprehension achievement between students who had high reading habit taught by using story mapping strategy and those who were taught by using traditional teaching method. Fourth, there was not any significant difference in reading comprehension achievement between students who had low high reading habit taught by using story mapping strategy and those who were taught by using traditional teaching method. And the last, there was significant interaction effect of story mapping strategy and reading habit on reading comprehension achievement of the eighth grade students of SMP N 35 Palembang.Keywords : Story Mapping Strategy, Students’ Reading Habit, Reading Comprehension Achievement.